AN ANALYSIS OF PERSONAL FACTORS AFFECTING LEARNING MOTIVATION: A RESEARCH ON THE ONLINE EDUCATION PROCESS DURING COVID-19 PERIOD IN TURKIYE - ISMAN, Aytekin; SABUNCUOGLU INANC, Ayda; AKINCI COTOK, Nesrin (The Turkish online journal of distance education TOJDE, 2023)
In 2019 Covid-19 appeared and spread quickly all over the world, affecting every structure of society, as well as the education system. One of the measures taken to prevent the further spread of the disease was mandatory online education at universities in Turkey. This sudden change has significantly affected students' learning motivations for face-to-face education. In this context, this study aims to determine the factors of arousal, beliefs, goals, and needs that affect the students' learning motivations as personal factors during online education in Turkey during the Covid-19 pandemic. For this aim, a semi-structured interview technique was used on a sample of 34 students. According to the findings, the internal factors on arousals were; mainly interest/curiosity and the external factors on arousals were mainly; compulsory attendance requirements. Also, the internal factors on success beliefs were mainly; determination, and the external factors mainly include motivational speeches. Besides, the internal factors on goals were mainly; the need to learn for the future, and the external factors on goals were mainly; homework and studies. Lastly, findings indicated that the internal needs of the students were mainly; success, and the external needs were mainly; communication